ANALISA TINGKAT KONTAMINASI DOSIS NUKLIR DAN LAJU PAPARAN RADIASI PADA INSTALASI KEDOKTERAN NUKLIR - Rafli Filano; Eko Hidayanto; Zaenal Arifin (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
The research has been analyzed the level of nuclear contamination and radiation exposure rate at installation of nuclear medicine with efforts a radiation protection is the prevention or decrease the number of entry of radioactive material into the human body. The method used to conduct measurement a count of contamination of surface work area resulting from the use of radioactive substances and carried out at a distance of 0.5 cm between the detector window with contaminated areas, while measuring the radiation exposure rate in each of center room at height of 1 meter from the surface of the floor in various rooms installation of nuclear medicine. The results of measurement obtained levels of contamination nuclear dose in various rooms installation of nuclear medicine is from 0,16 to 243 Bq/cm2 were classified as low to high levels of contamination. While the results of measurements of the radiation exposure rate is from 0,026 to 1,693μSv/h, which is classified as below the allowable dose value level, so it is still safe for radiation workers and other patients. Keywords: Radiation Protection, Radioactive, Contamination, Radiation Exposure Rate, Nuclear Medicine